The effect of antiretroviral therapy initiation on vitamin D levels and four oral diseases among Kenyan children and adolescents living with HIV. - Ana Lucia Seminario; Arthur Kemoli; Walter Fuentes; Yan Wang; Poojashree Rajanbabu; Dalton Wamalwa; Sarah Benki-Nugent; Grace John-Stewart; Jennifer A Slyker (PLoS ONE, 2022)
Objectives The impact of antiretroviral treatment (ART) on the occurrence of oral diseases among children and adolescents living with HIV (CALHIV) is poorly understood. The aim of this study was to determine the effect of ART timing on vitamin D levels and the prevalence of four oral diseases (dry mouth, dental caries, enamel hypoplasia, and non-herpes oral ulcer) among Kenyan CALHIV from two pediatric HIV cohorts. Methods This nested cross-sectional study was conducted at the Kenyatta National Hospital, Nairobi, Kenya. CALHIV, 51 with early-ART initiated at <12 months of age and 27 with late-ART initiated between 18 months-12 years of age, were included. Demographics, HIV diagnosis, baseline CD4 and HIV RNA viral load data were extracted from the primary study databases. Community Oral Health Officers performed oral health examinations following standardized training. Results Among 78 CALHIV in the study, median age at the time of the oral examination was 11.4 years old and median ART duration at the time of oral examination was 11 years (IQR: 10.1, 13.4). Mean serum vitamin D level was significantly higher among the early-ART group than the late-ART group (29.5 versus 22.4 ng/mL, p = 0.0002). Children who received early-ART had a 70% reduction in risk of inadequate vitamin D level (<20 ng/mL), compared to those who received late-ART (p = 0.02). Although both groups had similar prevalence of oral diseases overall (early-ART 82.4%; late-ART 85.2%; p = 0.2), there was a trend for higher prevalence of dry mouth (p = 0.1) and dental caries (p = 0.1) in the early versus late ART groups. The prevalence of the four oral diseases was not associated with vitamin D levels (p = 0.583). Conclusions After >10 years of ART, CALHIV with early-ART initiation had higher serum vitamin D levels compared to the late-ART group. The four oral diseases were not significantly associated with timing of ART initiation or serum vitamin D concentrations in this cohort. There was a trend for higher prevalence of dry mouth and dental caries in the early-ART group, probably as side-effects of ART.